2023
DOI: 10.1002/tox.23813
|View full text |Cite
|
Sign up to set email alerts
|

Exosome‐derived miR‐142‐5p from liver stem cells improves the progression of liver fibrosis by regulating macrophage polarization through CTSB

Abstract: Background This study aims to explore the effect of liver stem cells (LSCs)‐derived exosomes and the miR‐142a‐5p carried by them on the process of fibrosis by regulating macrophages polarization. Methods In this study, CCL4 was used to establish liver fibrosis model. The morphology and purity of exosomes (EVs) were verified by transmission electron microscopy, western blotting (WB) and nanoparticle tracing analysis (NTA). Real‐time quantitative PCR (qRT‐PCR), WB and enzyme‐linked immunoadsorption (ELISA) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…This results in decreased markers of M1 macrophage polarisation and increased markers of M2 macrophage polarisation. 75 Gingival tissue-derived MSCs (GMSCs) are Open access the mesenchymal stem cells of dental origin, with unique immunoregulatory capacity and secrete large amounts of EVs. 76 In a recent study, Watanabe et al found that EVs derived from GMSCs primed with a combination of two proinflammatory cytokines, TNF-α and interferon-α, synergistically promote anti-inflammatory M2 macrophage polarisation by increasing the expression of cluster of differentiation 73 (CD73) and CD5 molecule-like in EVs, which are mediated by mammalian target of rapamycin hypoxia-inducible factor-1α axis.…”
Section: Targeting Kcs In Liver Fibrosismentioning
confidence: 99%
“…This results in decreased markers of M1 macrophage polarisation and increased markers of M2 macrophage polarisation. 75 Gingival tissue-derived MSCs (GMSCs) are Open access the mesenchymal stem cells of dental origin, with unique immunoregulatory capacity and secrete large amounts of EVs. 76 In a recent study, Watanabe et al found that EVs derived from GMSCs primed with a combination of two proinflammatory cytokines, TNF-α and interferon-α, synergistically promote anti-inflammatory M2 macrophage polarisation by increasing the expression of cluster of differentiation 73 (CD73) and CD5 molecule-like in EVs, which are mediated by mammalian target of rapamycin hypoxia-inducible factor-1α axis.…”
Section: Targeting Kcs In Liver Fibrosismentioning
confidence: 99%
“… 101 In another study, scientists examined changes in exosomes produced by liver stem cells in a CCl 4 -induced fibrosis model, and they identified the increased expression of miR-142a-5p, which prevents macrophages toward M1 polarization and facilitated the production of M2 markers through targeting cathepsin B to suppress LF in mice. 102 …”
Section: Exosomes Targeting Macrophages and Their Roles In Lfmentioning
confidence: 99%
“…101 In another study, scientists examined changes in exosomes produced by liver stem cells in a CCl 4 -induced fibrosis model, and they identified the increased expression of miR-142a-5p, which prevents macrophages toward M1 polarization and facilitated the production of M2 markers through targeting cathepsin B to suppress LF in mice. 102 Artificial exosome system: Artificial exosomes have been explored to treat LF in recent decades. Contemporary scholarly investigations are mainly concentrated on utilizing unaltered or modified exosomes as an innovative approach for drug administration, explicitly targeting the liver to deliver antifibrotic medications with precision.…”
Section: Exosomes Targeting Macrophages To Inhibit Lfmentioning
confidence: 99%
See 1 more Smart Citation